2014
DOI: 10.1007/s12010-014-1438-5
|View full text |Cite
|
Sign up to set email alerts
|

Isolation of a Ribonuclease with Antiproliferative and HIV-1 Reverse Transcriptase Inhibitory Activities from Japanese Large Brown Buckwheat Seeds

Abstract: A ribonuclease, with a molecular mass of 22.5 kDa and an N-terminal sequence exhibiting resemblance to previously isolated buckwheat storage proteins and allergens, was isolated from Japanese large brown buckwheat seeds. The ribonuclease was purified using a simple protocol that comprised ion exchange chromatography on Q-Sepharose and DEAE-cellulose and gel filtration on Superdex 75. The ribonuclease exhibited low activity toward poly U, lower activity toward poly C, and very low activity toward poly A and pol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…Flavonoids, ,, polysaccharides, lectins, and phenylpropanoids , from BW have been shown to induce apoptotis, differentiation, and cytotoxicity against a wide range of cancer cell lines in vitro. In a recent study, Yuan et al observed that a ribonuclease isolated from BW seeds inhibited the proliferative activity of HepG2 (IC 50 = 79.2 μM) and MCF-7 (IC 50 = 63.8 μM) cancer cells . BW proteins have also been revealed to exert anticancer activity.…”
Section: Health Benefits and Buckwheatmentioning
confidence: 99%
See 1 more Smart Citation
“…Flavonoids, ,, polysaccharides, lectins, and phenylpropanoids , from BW have been shown to induce apoptotis, differentiation, and cytotoxicity against a wide range of cancer cell lines in vitro. In a recent study, Yuan et al observed that a ribonuclease isolated from BW seeds inhibited the proliferative activity of HepG2 (IC 50 = 79.2 μM) and MCF-7 (IC 50 = 63.8 μM) cancer cells . BW proteins have also been revealed to exert anticancer activity.…”
Section: Health Benefits and Buckwheatmentioning
confidence: 99%
“…In a recent study, Yuan et al observed that a ribonuclease isolated from BW seeds inhibited the proliferative activity of HepG2 (IC 50 = 79.2 μM) and MCF-7 (IC 50 = 63.8 μM) cancer cells. 123 BW proteins have also been revealed to exert anticancer activity. As reviewed by de Mejia and Dia, isolated BWPs such as BW protease inhibitors (BWI-1 and BWI-2a) and the recombinant form of BWI-1 (rBWI-1) have anticancer activity, evidenced mainly by induction of apoptosis and growth inhibition against a wide range of cancer cell models.…”
Section: Journal Of Agricultural and Food Chemistrymentioning
confidence: 99%
“…Peptide mimics of other RT binding viral proteins, such as a Vpr protein-derived peptide, also hold promise as peptide inhibitors [183] . Other peptide inhibitors for RT include peptides derived from ribonuclease [184] , [185] , polyarginine transporter molecules [186] , N-methylated peptides that bind RNA [187] , protein targeting RTC [188] , and anti-fungal peptides [189] . Similarly to protease and integrase peptide inhibitors, RT peptide inhibitors also face the problem of low potency (high IC50 values) and thus have not advanced to in vivo evaluation or clinical studies.…”
Section: Targets Of Peptide Inhibitors [154] mentioning
confidence: 99%
“…Recent research has found that buckwheat seed extract has strong antioxidant activity (Lin et al 2002). In addition, immunostimulant and antivirulant activities of seeds have been noted (Bai et al 2015; Yuan et al 2015). Besides the work of Sipes and Arakaki dealing with the nematicidal activity of buckwheat against Meloidogyne javanica (Sipes et al 1997), there is no available report on the nematicidal activity of F. esculantum on M. incognita , the most widespread Meloidogyne species.…”
Section: Introductionmentioning
confidence: 99%